(untitled) (Research, Society and Development, 2024)
Objective: To describe part of the epidemiological profile of hospitalizations and deaths due to diarrhea and gastroenteritis of presumed infectious origin in the 1st Health Region (Paranaguá) in the eastern macro-region of the State of Paraná between the years 2013 to 2023, reflecting the importance of primary health care . Methodology: This is a retrospective epidemiological descriptive study, based on secondary data, from the Hospital Information System (SIH), in DATASUS. Results: 622 hospital admissions were cataloged for ‘’Diarrhea and Gastroenteritis of Presumed Infectious Origin’’, CID: (A09), considering public and private hospitals, and all categories of care. Of these, 12 records resulted in death within the time frame. Ethnicity, predominantly mentioned, was the non-specific variable described as ‘’no information’’ and the race/color variable ‘’white’’. The genders highlighted in hospitalizations in these periods were male, although this was not significant in terms of deaths. As for the age group, between 1 and 4 years old stood out, presenting the highest number of hospitalizations, followed by the age group of 5 to 9 years old. However, there was a divergence for the age group in cases of deaths, with a predominance of those over 40 years old. In the regional health department, the municipality of Paranaguá presented more than 50% of hospitalizations. The variables relating to the average length of stay of hospitalizations, the values ​​of hospital services, average values ​​of hospitalizations and mortality rate were also presented. Conclusion: Therefore, in the period surveyed, inadequate basic sanitation, access to health services and environmental education can be inferred as one of the main risk factors.